2008
DOI: 10.1177/154405910808700312
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Human Dental Pulp Stem Cell Differentiation by Notch Signaling

Abstract: Notch signaling plays a critical role in development and cell fate specification. Notch receptors and ligands have been found to be expressed in dental epithelium or mesenchyme in the developing tooth, suggesting that Notch signaling may regulate odontogenesis. Post-natal human dental pulp stem cells (DPSCs) isolated from the dental pulp have characteristics of mesenchymal stem cells and can differentiate into odontoblasts. In this study, we examined whether Notch signaling regulated the odontoblastic differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
64
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 23 publications
3
64
0
2
Order By: Relevance
“…Notch-1 triggers differentiation and inhibits growth of human keratinocytes in vitro. In the odontogenic tissues, the activation of the Notch signaling may inhibit the differentiation of pulp stem cells into odontoblasts (21), indicating distinct roles of this pathway depending on the analyzed tissue. Genetic deletion of the Notch system in human keratinocytes is sufficient, along with the activation of the ras gene to cause aggressive squamous cell carcinomas (22).…”
Section: Discussionmentioning
confidence: 99%
“…Notch-1 triggers differentiation and inhibits growth of human keratinocytes in vitro. In the odontogenic tissues, the activation of the Notch signaling may inhibit the differentiation of pulp stem cells into odontoblasts (21), indicating distinct roles of this pathway depending on the analyzed tissue. Genetic deletion of the Notch system in human keratinocytes is sufficient, along with the activation of the ras gene to cause aggressive squamous cell carcinomas (22).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of Notch signaling by Delta1 ligand can enhance the proliferation and odontogenic ability of DPSCs due to the increasing of the proliferation index (PI), DSPP protein expression level and calcifi ed nodules number in Delta1-DPSCs [ 48 ]. However, another study reports that the activation of Notch signaling by either Jagged1 or N1ICD can depress the differentiation of DPSCs into odontoblasts without interrupting cell proliferation [ 92 ]. In addition, Notch signaling pathway modulates the osteogenic differentiation of dental follicle stem cells (DFSCs) [ 93 ].…”
Section: Other Signaling Pathwaysmentioning
confidence: 99%
“…The odontogenic differentiation potential, the origin from pulp tissue or precursor tissue, and the ability to readily isolate from freshly extracted teeth are the most striking features that make DPSCs a possible candidate for pulp/dentin regeneration (2,3). Previous studies have shown that DPSCs can produce dentin/pulp-like tissues after implantation into tooth slices/fragments and transplantation subcutaneously in immunocompromised mice (4,5).…”
mentioning
confidence: 99%